Review of Coordinated Control Strategy for Hybrid Type Wind Farms Under Network Faults - Dr. A. Ramkumar, K. Karthi, Dr. K. Rajesh (International Journal of Advanced Science and Technology, 2020)
This paper represents the comprehensive review of coordinated control objective of hybrid type wind farms comprising of the Doubly Fed Induction Generators (DFIG) and Permanent Magnet Synchronous Generator (PMSG) under network faults. The ability of DFIG and PMSG on negative sequence currents during the course of grid network unbalance also presented. The capability of the negative sequence current of the DFIG and PMSG is presented in this paper. The regions of controllability of DFIG and PMSG are also depicted in this paper. The different control objectives for DFIG RSC & GSC as well as PMSG are analyzed in detail.